PERKEMBANGAN DEFINISI DAN KAWASAN TEKNOLOGI PEMBELAJARAN SERTA PERANNYA DALAM PEMECAHAN MASALAH PEMBELAJARAN - Bambang Warsita (Balai Besar Guru Penggerak Jawa Timur, 2013)
The formulation definition of intructional technologies has undergone several changes throughout history and development of the field scope and profession of intructional technologies. The fields of intructional technologies include the design, development, utilization, management, assessment and research processes, and also learning resources and systems. Definition and the field of intructional technology is theoretical study. The role of intructional technologies in solving learning problems is a practical and applied field of study. It is associated with the use of intructional technologies in facilitating human learning. Both as knowledge discipline and study program or profession, intructional technology continues to experience rapid growth.AbstrakRumusan definisi teknologi pembelajaran telah mengalami beberapa kali perubahan, sejalan dengan sejarah dan perkembangan dari ruang lingkup bidang garapan dan profesi teknologi pembelajaran. Kawasan teknologi pembelajaran meliputi desain, pengembangan, pemanfaatan, pengelolaan, penilaian dan penelitian proses, sumber dan sistem untuk belajar. Definisi dan kawasan teknologi pembelajaran merupakan kajian teori. Peran teknologi pembelajaran dalam pemecahan masalah-masalah pembelajaran merupakan kajian praktis dan terapan. Artinya berkaitan dengan pemanfaatan teknologi pembelajaran dalam memfasilitasi belajar manusia. Teknologi pembelajaran baik sebagai disiplin ilmu, program studi maupun profesi terus mengalami perkembangan yang pesat.